2000
DOI: 10.1088/0963-0252/9/2/311
|View full text |Cite
|
Sign up to set email alerts
|

Effect of different elementary processes on the breakdown in low-pressure helium gas

Abstract: We investigated the breakdown in low-pressure helium gas both experimentally and by computer simulations. At low breakdown voltages (V BR 1000 V) the experimental and simulation results show a good agreement (differences are within 20%), while at higher voltages the simulations and experiments agree qualitatively. Our simulations indicate that several processes contribute to the particular shape of the Paschen curve in helium at low pressures. These processes are: (1) the dependence of the (ion-induced) second… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
42
0

Year Published

2006
2006
2017
2017

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 62 publications
(45 citation statements)
references
References 45 publications
3
42
0
Order By: Relevance
“…The code is still under development but important features of the discharges in helium can already be reproduced. [9]. The region in which the simulations predict an enhanced secondary electron production follows this border line.…”
Section: Breakdown Calculationsmentioning
confidence: 80%
See 2 more Smart Citations
“…The code is still under development but important features of the discharges in helium can already be reproduced. [9]. The region in which the simulations predict an enhanced secondary electron production follows this border line.…”
Section: Breakdown Calculationsmentioning
confidence: 80%
“…Electrical breakdown in gases is one of the most fundamental phenomena in gas discharge physics. For plane-parallel electrode arrangements it has been found that the breakdown voltage is a function of the product of gas pressure (p) and electrode separation (d), V BR = f (pd) [9]. While discharges in the case of static (DC) potentials have been studied widely, information on discharges in the case of RF voltages is scarce.…”
Section: Minimizing Electrical Breakdownsmentioning
confidence: 99%
See 1 more Smart Citation
“…Earlier developed models of breakdown in helium [8] are not able to explain such ultra-fast development of current. The electron emission from the cathode due to ions/fast atoms bombardment is usually considered as a main process of breakdown development in abnormal glow discharge.…”
Section: Introductionmentioning
confidence: 94%
“…Available papers contain a broad range of conditions for igniting a self-sustained rf discharge in various gases (see, e.g., [8][9][10][11] and the references cited therein). Dc discharge ignition is also studied in sufficient detail, e.g., in [12][13][14][15][16]. But the question of igniting a longitudinal combined discharge was not subjected to such a broad study.…”
Section: Introductionmentioning
confidence: 99%